Intrahepatic Cholestasis Following Abuse of Powdered Kratom (Mitragyna speciosa) - Kapp, Friedrich G. (Springer-Verlag, 2011)
INTRODUCTION: Kratom (Mitragyna speciosa) is a common medical plant in Thailand and is known to contain mitragynine as the main alkaloid. According to an increase in published reports and calls at German poison control centers, it has been used more frequently as a drug of abuse in the western hemisphere during the last couple of years. Despite this increase, reports of severe toxicity are rare within the literature. CASE REPORT: We describe a case of a young man who presented with jaundice and pruritus after intake of kratom for 2 weeks in the absence of any other causative agent. Alkaloids of M. speciosa were detected in the urine. CONCLUSION: While M. speciosa is gaining in popularity among illicit drug users, its adverse effects remain poorly understood. This is the first published case of intrahepatic cholestasis after kratom abuse.